Path-analytic study of cognitive entry characteristic and students' achievement in bearing in mathematic (2009)
Individual differences in learning outcomes have-been observed by many researchers in the past. Bloom (1974) proposed that the Cognitive Entry Characteristics are alterable variables that account for the greatest degree of variance in students' learning.This study, therefore, validated a causal model that involved Cognitive Entry Characteristics (CEC) and student achievement in bearing in Mathematics. The study is an ex-post facto type. Four hundred and ninety two SS 3 students were involved in the study. The samples were drawn using multi-stage sampling technique from public co-educational secondary schools in three of the five local government areas in Ibadan metropolis. The instruments used for data collection were the Mathematics Achievement Test (r = 0.80, P = 0.4) and Diagnostic Tests measuring the CECs. The data collected were analysed using path analysis ( a path between causal factor and dependent variable was retained if /Pji/≥ 0.05 and rij is significant at 0.05 aplha level) The study revealed that all the hypothesized CEC were found to have either direct or indirect effect or both on students' achievement in bearing . This has implications for education, especially the curriculum developers and classroom teachers, particularly on the need for learning sequence. It was therefore recommended that equipping students with adequate level of cognitive entry characteristics that would enhance high degree of cognitive achievement be considered by teachers.